Application of femoral nerve block combined with modified swelling anesthesia in high ligation and stripping of great saphenous vein - Chen, Xiaobin; Liu, Zhenwen; Zhou, Binbin; Fan, Zuyou; Zhao, Hu; Lin, Chen (Frontiers in Surgery, 2023)
Background To analyze and explore the clinical efficacy of ultrasound guided femoral nerve block combined with modified swelling anesthetic solution in high ligation and stripping of the great saphenous vein. Methods 90 patients with varicose great saphenous vein of lower limbs undergoing high ligation and stripping of great saphenous vein were randomly divided into group A (femoral nerve block combined with modified swelling anesthesia), group B (simple swelling anesthesia) and group C (epidural anesthesia), with 30 patients in each group. The serum CRP level, operation duration, intraoperative blood loss, postoperative hospitalization time, total hospitalization cost, postoperative VAS score, preoperative and postoperative VCSS score, intraoperative mean arterial pressure and heart rate, postoperative related complications, and patients, satisfaction with diagnosis and treatment were compared among the three groups. Results There was no significant difference in operation duration, intraoperative blood loss, postoperative complications, and preoperative and postoperative VCSS scores among the three groups (P > 0.05). The postoperative hospitalization time, postoperative VAS score and total hospitalization cost of patients in group A and B were lower than those in group C, and the postoperative hospitalization time and postoperative VAS score in group A were more significant (P < 0.05). Compared with group B, the fluctuation range of intraoperative mean arterial pressure and heart rate, and postoperative serum CRP level in group A and C were lower, especially in group A (P < 0.05). The three groups of patients were followed up regularly after surgery. The results showed that the number of postoperative complications in group A was lower than that in the other two groups (P < 0.05), and the postoperative complications of the three groups were effectively relieved after symptomatic treatment (dressing change, anti-infection, taking drugs to improve circulation, etc.). The satisfaction of patients in group A was significantly higher than that in groups B and C (P < 0.05). Conclusions Ultrasound guided femoral nerve block combined with modified swelling anesthetic solution applied in high ligation and stripping of the great saphenous vein can significantly improve postoperative inflammatory stress reaction of patients, effectively ensure the safety and reliability of surgical progress, help to improve analgesia effect and accelerate physical rehabilitation, and has short hospitalization time, low medical cost, and high satisfaction of patients' diagnosis and treatment, which is worthy of widespread clinical promotion and reference.